A positive correlation between energetic electron butterfly distributions and magnetosonic waves in the radiation belt slot region. Issue 9 (14th May 2017) - Yang, Chang; Su, Zhenpeng; Xiao, Fuliang; Zheng, Huinan; Wang, Yuming; Wang, Shui; Spence, H. E.; Reeves, G. D.; Baker, D. N.; Blake, J. B.; Funsten, H. O.
Abstract: Energetic (hundreds of keV) electrons in the radiation belt slot region have been found to exhibit the butterfly pitch angle distributions. Resonant interactions with magnetosonic and whistler‐mode waves are two potential mechanisms for the formation of these peculiar distributions. Here we perform a statistical study of energetic electron pitch angle distribution characteristics measured by Van Allen Probes in the slot region during a 3 year period from May 2013 to May 2016. Our results show that electron butterfly distributions are closely related to magnetosonic waves rather than to whistler‐mode waves. Both electron butterfly distributions and magnetosonic waves occur more frequently at the geomagnetically active times than at the quiet times. In a statistical sense, more distinct butterfly distributions usually correspond to magnetosonic waves with larger amplitudes and vice versa. The averaged magnetosonic wave amplitude is less than 5 pT in the case of normal and flat‐top distributions with a butterfly index BI =1 but reaches ∼50–95 pT in the case of distinct butterfly distributions with BI >1.3. For magnetosonic waves with amplitudes >50 pT, the occurrence rate of butterfly distribution is above 80%. Our study suggests that energetic electron butterfly distributions in the slot region are primarily caused by magnetosonic waves. Key Points: Electron butterfly distributions occur more frequently at the geomagnetically active times than at the quite times A positive relation between magnetosonic waves and electron butterfly distributions No close relation between whistler‐mode waves and electron butterfly distributions